Pengaruh Kepercayaan Diri dan Efikasi Diri terhadap Niat Berwirausaha : (Survei Pada Mahasiswa Tingkat Akhir Prodi Manajemen Universitas Islam Bandung) - Aji Moch Panji Wardhana; Rusman Frendika; Allya Roosallyn Assyofa (Bandung Conference Series: Business and Management, 2022)
Abstract. One of the benchmarks for the progress of a nation is to look at the size of the composition of entrepreneurs in the structure of society. However, this composition has not been achieved by Indonesia because the community, especially Indonesian youth, are still not aware of entrepreneurship. According to the Expert Staff for the Creative Economy of the Ministry of Youth and Sports, the interest in entrepreneurship of Indonesian youth is still relatively low. Therefore, this study is about the effect of self-confidence and self-efficacy on entrepreneurial intentions, the purpose of which is to find out how the level of self-confidence, the level of self-efficacy, entrepreneurial intentions, the effect of self-confidence on entrepreneurial intentions, the effect of self-efficacy on entrepreneurial intentions, and the effect of self-confidence and self-efficacy towards entrepreneurial intentions. The research method used in this research is descriptive verification. Data collection techniques in this study by conducting questionnaires, interviews and collecting documents related to research. Analysis of the data used by using simple linear regression analysis, multiple linear regression, t-test and F-test with a total sample of 425 respondents. The results of this study are that the responses of Unisba Study Program students regarding the level of self-confidence are moderate/adequate, Unisba Study Program students' responses regarding the level of self-efficacy are moderate/sufficient, Unisba Study Program students' responses regarding entrepreneurial intentions are moderate/sufficient, and self-confidence has an effect on entrepreneurial intentions. Unisba Management Study Program student. Likewise, self-efficacy affects the entrepreneurial intentions of Unisba Management Study Program students. As for the influence of self-confidence and self-efficacy simultaneously on the entrepreneurial intention of Unisba Management Study Program students. Abstrak. Salah satu tolak ukur bagi kemajuan suatu bangsa adalah dengan melihat besarnya komposisi wirausahawan dalam struktur masyarakat. Namun, komposisi tersebut belum dapat dicapai oleh Indonesia karena masyarakat khususnya pemuda Indonesia yang masih belum sadar untuk berwirausaha. Menurut Staf Ahli Bidang Ekonomi Kreatif Kementerian Pemuda dan Olah Raga bahwa minat berwirausaha pemuda Indonesia masih relatif cukup rendah. Maka dari itu penelian ini mengenai Pengaruh Kepercayaan Diri Dan Efikasi Diri Terhadap Niat Berwirausaha yang tujuannya adalah untuk mengetahui bagaimana tingkat kepercayaan diri, tingkat efikasi diri, niat berwirausaha, pengaruh kepercayaan diri terhadap niat berwirausaha, pengaruh efikasi diri terhadap niat berwirausaha, dan pengaruh kepercayaan diri dan efikasi diri terhadap niat berwirausaha. Metode penelitian yang digunakan dalam penelitian ini deskriptif verifikatif. Teknik pengumpulan data dalam penelitian ini dengan melakukan kuisioner, wawancara dan pengumpulan dokumen-dokumen yang berkaitan dengan penelitian. Analisis data yang digunakan dengan menggunakan analisis regresi linier sederhana, regresi linier berganda, uji-t dan uji F dengan jumlah sample sebanyak 425 Responden. Hasil dari penelitian ini adalah tanggapan mahasiswa Prodi Unisba mengenai tingkat kepercayaan diri adalah sedang/cukup, tanggapan mahasiswa Prodi Unisba mengenai tingkat efikasi diri adalah sedang/cukup, tanggapan mahasiswa Prodi Unisba mengenai niat berwirausaha adalah sedang/cukup, serta kepercayaan diri berpengaruh terhadap niat berwirausaha mahasiswa Prodi Manajemen Unisba. Begitupun pada efikasi diri berpengaruh terhadap niat berwirausaha mahasiswa Prodi Manajemen Unisba. Adapun pun pengaruh kepercayaan diri dan efikasi diri secara simultan terhadap niat berwirausaha mahasiswa Prodi Manajemen Unisba.